The Influence of Training, Communication, and Work Environment on Employee Performance at Pt. Lestari Dini Tunggul - Affiani, Ariqoh Eka; Krisnandi, Herry; Digdowiseiso, Kumba (International Journal of Social Service and Research, 2023)
This study aims to determine and analyze the effect of Training, Communication, and Work Environment on Employee Performance at PT. Lestari Dini Tunggul. This research includes quantitative research, where the research instrument is a questionnaire. The sample in this study are employees at PT. Lestari Dini Tunggul with a total of 92 employees. The instrument test in this study was directed to use validity and reliability tests. The data analysis method uses inferential analysis with multiple linear regression and uses the Statistical Product and Service Solution (SPSS) version 23.0 program. The results of multiple linear regression analysis show that the variables Training (X1), Communication (X2), and Work Environment (X3) have a positive and significant effect on Employee Performance (Y). The results of this study are expected that PT. Lestari Dini Tunggul is able to pay attention to Training, Communication, and Work Environment in order to improve Employee Performance.